2006
DOI: 10.1634/stemcells.2005-0342
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Mesenchymal Stem Cells from Bone Marrow, Umbilical Cord Blood, or Adipose Tissue

Abstract: Mesenchymal stem cells (MSCs) represent a promising tool for new clinical concepts in supporting cellular therapy. Bone marrow (BM) was the first source reported to contain MSCs. However, for clinical use, BM may be detrimental due to the highly invasive donation procedure and the decline in MSC number and differentiation potential with increasing age. More recently, umbilical cord blood (UCB), attainable by a less invasive method, was introduced as an alternative source for MSCs. Another promising source is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

120
2,197
7
88

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 2,910 publications
(2,412 citation statements)
references
References 37 publications
120
2,197
7
88
Order By: Relevance
“…Allogeneic transplantation of MSCs may have a logistic advantage because they are ready to use “off the shelf” in the clinical setting. Moreover, UCB‐derived MSCs exhibit several advantages over adult tissue‐derived MSCs including lower immunogenicity 16, 36 and higher proliferation capacity, paracrine potency, and therapeutic efficacy both in vitro 17, 18 and in vivo 37. These MSCs show karyotypic stability and no senescence up to the 11th passage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allogeneic transplantation of MSCs may have a logistic advantage because they are ready to use “off the shelf” in the clinical setting. Moreover, UCB‐derived MSCs exhibit several advantages over adult tissue‐derived MSCs including lower immunogenicity 16, 36 and higher proliferation capacity, paracrine potency, and therapeutic efficacy both in vitro 17, 18 and in vivo 37. These MSCs show karyotypic stability and no senescence up to the 11th passage.…”
Section: Discussionmentioning
confidence: 99%
“…Human umbilical cord blood (UCB) is a promising source of MSCs. In comparison to adult tissue‐derived MSCs, its advantages include easier extraction, lower immunogenicity 16, higher in vitro proliferation capacity 17, 18, and better in vivo therapeutic efficacy 19. Recently, we have shown that xenotransplantation of human UCB‐derived MSCs significantly attenuates brain injury and the progress of PHH after severe IVH in immunocompetent newborn rats 15, 20, 21.…”
Section: Introductionmentioning
confidence: 99%
“…In 1961, Hayflick and Moorhead discovered that in vitro, human skin fibroblasts undergo only a limited number of population doublings (termed Hayflick limit), and that this number decreased with increasing donor age (Hayflick and Moorhead, 1961). Similar to other human diploid cells, MSC exhibit replicative senescence in vitro, as demonstrated by a number of investigators (Fehrer et al, 2007;Kern et al, 2006;Stenderup et al, 2003;Stenderup et al, 2004;Stolzing et al, 2008). The in vitro senescent phenotype includes the following characteristic features: (i) irreversible arrest of cell division (in contrast to quiescence, where this lock is reversible), (ii) resistance to apoptotic death, and (iii) the excretion of molecules normally secreted during wound repair and infection, such as inflammatory cytokines, proteases and growth factors, the latter having detrimental consequences for the surrounding tissue (Campisi, 2001).…”
Section: Msc In Vitro Senescencementioning
confidence: 99%
“…The in vitro senescent phenotype includes the following characteristic features: (i) irreversible arrest of cell division (in contrast to quiescence, where this lock is reversible), (ii) resistance to apoptotic death, and (iii) the excretion of molecules normally secreted during wound repair and infection, such as inflammatory cytokines, proteases and growth factors, the latter having detrimental consequences for the surrounding tissue (Campisi, 2001). Some, but not all of these characteristics have also been described for MSC cultures (Fehrer et al, 2007;Kern et al, 2006;Stenderup et al, 2003;Stenderup et al, 2004;Stolzing et al, 2008)…”
Section: Msc In Vitro Senescencementioning
confidence: 99%
“…Si, en ce domaine, il n'existe pas d'exigence de la part des autorités de régula-tion, il faudra se pencher sur ce problème, surtout en cas d'utilisation de donneurs dits uniques. De nombreux tissus sont des sources potentielles de CSM : la moelle osseuse, le tissu adipeux et le sang de cordon sont les plus utilisés actuellement [6]. La moelle osseuse et le tissu adipeux sont d'accès facile, et les CSM -dont la quantité est estimée par le nombre de CFU-F mesuré en culture -sont plus abondantes dans le tissu adipeux que dans la moelle osseuse [35] (➜).…”
Section: Le Matériel De Départunclassified